2022
DOI: 10.1155/2022/5792866
|View full text |Cite|
|
Sign up to set email alerts
|

Ferroptosis in Macrophage Impairment in Sepsis

Abstract: Sepsis is a clinical syndrome with high mortality, which can lead to multiple organ dysfunction syndrome. Nonspecific immune dysfunction and immune imbalance are its important pathological features. Macrophages are important immune cells and one of the important components of innate and adaptive immunity. Regulating the function of macrophages may be a potential method for the treatment of sepsis. Up to now, ferroptosis has been proved to be involved in the pathophysiological mechanism of many diseases, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Our data also demonstrated that the level of ferroptosis in CD68 + macrophages (or the number of CD68 + -4-HNE + macrophages/field) was decreased by administration of the Piezo1 inhibitor (GsMTx4), followed by a decline in the number of M1-like macrophages and improved lung injury in experimental MA-ALI mice. Our finding was similar to those of other previous reports, where uridine alleviated sepsis-induced acute lung injury by inhibiting ferroptosis of macrophages [ 52 ]; activated ferroptosis in macrophages contrarily accelerated the occurrence of sepsis [ 53 ]. Moreover, a previous study demonstrated that ferroptosis was triggered by increasing M1-like macrophages in neutrophilic airway inflammation, whereas quercetin decreased the level of ferroptosis in lung tissues by suppressing the pro-inflammatory M1-like macrophages [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our data also demonstrated that the level of ferroptosis in CD68 + macrophages (or the number of CD68 + -4-HNE + macrophages/field) was decreased by administration of the Piezo1 inhibitor (GsMTx4), followed by a decline in the number of M1-like macrophages and improved lung injury in experimental MA-ALI mice. Our finding was similar to those of other previous reports, where uridine alleviated sepsis-induced acute lung injury by inhibiting ferroptosis of macrophages [ 52 ]; activated ferroptosis in macrophages contrarily accelerated the occurrence of sepsis [ 53 ]. Moreover, a previous study demonstrated that ferroptosis was triggered by increasing M1-like macrophages in neutrophilic airway inflammation, whereas quercetin decreased the level of ferroptosis in lung tissues by suppressing the pro-inflammatory M1-like macrophages [ 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…The primary mechanism driving ferroptosis involves the catalytic activity of divalent iron or ester oxygenase, leading to heightened expression of unsaturated fatty acids on the cell membrane, ultimately causing lipid peroxidation and ensuing cellular demise. 44 Iron ions and ROS form crosstalk and mediate ferroptosis (figure 2C,D).…”
Section: Disturbances In Ros Metabolismmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%